2015
DOI: 10.1039/c5ra06692a
|View full text |Cite
|
Sign up to set email alerts
|

Improved photo-luminescence behaviour of Eu3+ activated CaMoO4 nanoparticles via Zn2+ incorporation

Abstract: Zn 2+ (0, 2, 5, 7 and 10 at.%) co-doped CaMoO 4 :2Eu 3+ nanophosphors have been synthesized via polyol method using ethylene glycol (EG) as both capping agent and reaction medium at 150 o C.From XRD analysis, all 900 C annealed, Zn-co-doped CaMoO 4 :Eu 3+ have tetragonal scheelite phase.Some extra phase evolution has been observed for ASP Zn doped samples. Intensity and crystallinity of XRD patterns increase as heat treatment increases to 900 C. Valence state of the involved compositions (Zn co-doped CaMoO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 43 publications
(90 reference statements)
3
14
0
2
Order By: Relevance
“…SrF 2 stands out as an excellent host for various lanthanide ions due to its wide transparency window in visible spectrum and further reduced multiphonon relaxation rates as compared to other hosts such as YPO 4 and CaMoO 4 . [15][16][17] The YPO 4 and CaMoO 4 hosts have relatively high multiphonon relaxation but they can be prepared at a very low temperature. 17,18 In SrF 2 crystals, lanthanide ions form clusters in SrF 2 as a result of the need for charge compensation when divalent Sr 2+ is substituted by trivalent Pr 3+ .…”
Section: +mentioning
confidence: 99%
“…SrF 2 stands out as an excellent host for various lanthanide ions due to its wide transparency window in visible spectrum and further reduced multiphonon relaxation rates as compared to other hosts such as YPO 4 and CaMoO 4 . [15][16][17] The YPO 4 and CaMoO 4 hosts have relatively high multiphonon relaxation but they can be prepared at a very low temperature. 17,18 In SrF 2 crystals, lanthanide ions form clusters in SrF 2 as a result of the need for charge compensation when divalent Sr 2+ is substituted by trivalent Pr 3+ .…”
Section: +mentioning
confidence: 99%
“…They are able to emit characteristic transitions of 4 F 9/2 → 6 H 15/2 (blue) and 4 F 9/2 → 6 H 13/2 (yellow). The blue 4 F 9/2 → 6 H 15/2 transition is magnetic dipole transition, which is not easily affected by the surrounding environment, while yellow 4 F 9/2 → 6 H 13/2 transition is a highly sensitive electric dipole transition influenced by the microscopic environment [8].…”
Section: Introductionmentioning
confidence: 97%
“…As one of the members of metal molybdates, CaMoO 4 has the C 4h 6 symmetry and I4 1 /a space group. In the lattice, each Mo atom is surrounded by four oxygen atoms forming [MoO 4 ] polyhedral while each Ca atom is besieged by eight oxygen atoms building [CaO 8 ] polyhedral [4]. Due to their unique structure, good thermal and chemical stability and perfect luminescence properties, CaMoO 4 is a favorable host and has been widely utilized in scintillators, solid state lasers, fluorescent lamps and catalysts, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…all [8] have observed a significant energy transfer from WO42-groups to Eu3+ ions. Singh et al [9] has codoped CaMoO4:Eu3+ nanophosphors with Zn2+ and have found that Zn co-doping (up to 10 at.%) in CaMoO4:Eu3+ matrix produces the high distortion and asymmetry and can modify the crystal field around Eu3+ ion as well as improve the PL intensity. Enhanced photoluminescence of 900 o C annealed samples has been found comparable with the one obtained for samples prepared by Zn-doping.…”
Section: Introductionmentioning
confidence: 98%